Caregiver Reports of Patient-Initiated Violence in Psychosis. (July 2014) - Onwumere, Juliana; Grice, Sarah; Garety, Philippa; Bebbington, Paul; Dunn, Graham; Freeman, Daniel; Fowler, David; Kuipers, Elizabeth
Objective: Aggressive behaviour in psychosis is not uncommon. Community provision for people with psychosis has left informal caregivers to take on a greater role in their care. However, few studies have explored links between patient-initiated violence in mental health caregiving relationships and caregiver functioning. Our study investigated caregiver reports of aggressive acts committed by their relative with psychosis and their links to caregiver appraisals of the caregiving relationship and caregiver outcomes. Method: Caregivers of patients with a recent relapse of psychosis, recruited to a psychological therapy trial, completed the audiotaped Camberwell Family Interview at baseline. This semi-structured interview includes questions on the quality of the relationship between caregiver and patient, and patient history of violence. Seventy-two transcripts of interviews were assessed for reports of patient-initiated violence. Results: One-half of the caregiver sample (52.9%) reported an incident of patient-initiated violence during their interview; 62.2% of these involved violence toward themselves, and 24.3% toward property. Reports of patient violence were associated with caregiver ratings of hostility expressed toward patients, lower self-esteem, and emotion-focused coping. People caring on their own were more likely to report incidents of patient violence. Younger patients, males, and inpatients were more frequently identified as having a history of this kind of violence. Conclusions: Our findings suggested that caregiver reports of patient-initiated violence in psychosis are not uncommon. Mental health staff need to be aware of the risks of such violence for caregivers of people with psychosis, and consider appropriate procedures for minimizing it.